The Impact of Different Levels of Physical Activity on Health among Middle-Aged and Elderly Chinese Adults - Jing GUAN; Guojun WANG; Chunli GENG (Tehran University of Medical Sciences, 2019)
Background: There is a lack of specific study of the impact of physical activities on middle-aged and elderly adults in developing countries. We aimed to investigate the causal impact of different levels of physical activity on self-rated health status for Chinese adults with an average age of 61 yr from years 2011 to 2015. Methods: China Health and Retirement Longitudinal Study (CHARLS) conducted by the Peking University of China was utilized which was a longitudinal database and thus allowed to control for the effect of unobserved individual heterogeneities. In this study, this control was carried out using fixed effect and propensity score matching methods. In addition, this study further took into consideration of the discrete feature of our response variable, self-rated health status, by applying an ordered logit model. Results: Participating in moderate-to-vigorous physical activity significantly increased individuals' self-rated health status (P<.05) whereas lower intensity physical activity did not increase individuals' self-rated health status. Conclusion: Moderate-to-vigorous physical activity is an important instrument to improve the health status of middle-aged and elderly population in China. Government should encourage people to involve in more moderate-to-vigorous physical activity as it is an efficient way to improve individuals' health status.